Ocena ryzyka inwestowania w spółki giełdowe sektora bankowego z wykorzystaniem metod taksonomicznych - Mentel, Grzegorz; Pisula, Tomasz; Wierzbińska, Maria (An Assessment of the Risk of Investing in the Stock Market Companies of the Banking Sector with Apply of the Taxonomical Methods, 2007)
Banks are financial institutions which operate in a specific risk conditions. One of the main problem is to find the answer to the question: How to determine the market risk of the investing in stock market companies of the banking sector? In this paper was made an attempt to assessment of the risk of investing in the stock market companies of the banking sector with use of two taxonomical procedures: TMAI (Taxonometrical Measure of Investment Attractivenes) and GDM (Generalized Distance Measure). Presented methods and obtained results are able to be helpful for the stock exchange investors when taking accurate and proper investment decisions to invest in financial instruments of stock market companies of the banking sector. All companies of the bank sector quoted on the Warsaw Stock Exchange were taken into consideration in the analysis. The analysis was made for the time period 2000-2006 year. The computer programs Statistica 7.1 and GDM for Windows 1.0 were used in the research.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 462-471